Macroglossia associated with 271 bp deletion in exon 50 of dystrophin gene - Malhotra Hardeep; Juyal Ratish; Malhotra Kiran; Shukla Rakesh (Annals of Indian Academy of Neurology, 2011)
Macroglossia is rare in patients of Duchenne muscular dystrophy (DMD), and its occurrence without any endocrinologic abnormality, seizures or an abnormal karyotype is even rarer. We describe a patient of DMD with isolated macroglossia with 271 bp deletion in exon 50 of the dystrophin gene and speculate a relationship in this regard.